Lifestyle changes for prevention of breast cancer - Hashemi, Seyed Hesam Bani (Electron Physician, 2014)
Breast cancer is the second most common cause of death from cancer among women. Lifestyle changes are shown to be important in the prevention of breast cancer. Diet, physical activity, smoking, alcohol use, and vitamin and mineral use are key factors influencing the risk of breast cancer among women. Because these factors are related to each other, it is difficult to assess their individual roles in breast cancer. Some of these factors are alterable, meaning that women can decrease their risk for breast cancer by changing their behavior. Breast cancer is associated with a high rate of mortality and morbidity among women. Therefore, it is logical to try to find ways to decrease the risk of developing breast cancer. Lifestyle changes seem to be an easy, effective, and economical way to help prevention breast cancer. In women with a confirmed breast cancer diagnosis who are under radiotherapy treatment after undergoing a mastectomy, lifestyle changes are still very important. Some factors, such as smoking cessation and prevention of weight gain, may improve the long-term survival chances of these patients. Therefore, ways to increase women’s knowledge about the role of lifestyle changes in the prevention of breast cancer and in the survival of patients with diagnosed breast cancer should be considered and studied.